2019
DOI: 10.1038/s41598-019-51769-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vision-related Quality of Life with Visual Function in Age-Related Macular Degeneration

Abstract: The purpose of this study was to assess which visual function measures are most strongly associated with vision-related quality of life (VRQoL) in age-related macular degeneration (AMD). A cross-sectional study of subjects with early AMD (n = 10), intermediate AMD (n = 42) and late AMD (n = 38) was conducted. Subjects were interviewed with the Impact of Vision Impairment (IVI) questionnaire. Functional tests performed included best-corrected visual acuity (BCVA), low luminance visual acuity (LLVA), visual acui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 33 publications
(37 reference statements)
2
41
0
Order By: Relevance
“…LLVA is hypothesised to be a better marker of everyday visual function under low light conditions than standard VA. And yet studies involving visually healthy, older age groups reported that neither LLVA nor LLD were associated with significant changes in quality of life measures or disability questionnaires 4,35,72 . This contrasts with AMD studies where quality of life measures correlated significantly with LLVA and LLD in all stages of the disease 16,19–21 …”
Section: Discussion and Critical Reviewmentioning
confidence: 98%
“…LLVA is hypothesised to be a better marker of everyday visual function under low light conditions than standard VA. And yet studies involving visually healthy, older age groups reported that neither LLVA nor LLD were associated with significant changes in quality of life measures or disability questionnaires 4,35,72 . This contrasts with AMD studies where quality of life measures correlated significantly with LLVA and LLD in all stages of the disease 16,19–21 …”
Section: Discussion and Critical Reviewmentioning
confidence: 98%
“…early and intermediate AMD). [1][2][3] In early and intermediate AMD, patients usually perform well in standard high contrast, high luminance best-corrected visual acuity (BCVA) testing. 4 However, the most widely used outcome measure in ophthalmic research is BCVA, 5,6 which appears to be largely insensitive to the specific functional impairment in early and intermediate AMD.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Various studies found a functional impairment beyond best-corrected central visual acuity, using electroretinography (ERG) testing and fundus-controlled perimetry (FCP) (also termed as microperimetry). [24][25][26][27][28][29][30][31][32] A reduction of multifocal electroretinography (mfERG) function was seen in areas of RPD by Alten and coworkers. 23 In addition increased rodintercept time (RIT) in presence of RPD was observed by Flamendorf et al, 33 whereas within a longitudinal observational period of 12 months RIT was shown to remain stable in eyes with AMD and RPD.…”
mentioning
confidence: 99%